Environmental enrichment as strategy to promote neurogenesis in Alzheimer disease: possible participation of phospholipase A2 (Archives of Clinical Psychiatry, 2010)
BACKGROUND: With the discovery that constitutive neurogenesis persists in the adult brain, has emerged the hypothesis in the literature that Alzheimer disease (AD) could be overcome, or at least ameliorated, since the generation of new neurons might help to compensate for the loss of neurons in the disease. OBJECTIVES: In this work the literature on endogenous neurogenesis in the brain of subjects with AD and animal models of AD, the effects of cognitive activity on neurogenesis, and the relationship between the enzyme phospholipase A2 (PLA2) and neurogenesis was reviewed. METHODS: MedLine database was searched using the keywords Alzheimer disease, cognitive activity, phospholipase A2, neurogenesis, and neuritogenesis. RESULTS: The literature review evidenced increased neuroproliferation in AD brain, however, the new neurons fail to differentiate into mature neurons. A non-pharmacological strategy, enriched environment, increases neurogenesis (including neuronal maturation) in experimental animals. Relationship between PLA2 and neurogenesis has been demonstrated in in vitro and in vivo experimental models. DISCUSSION: The data indicate that environmental enrichment (with cognitive and physical stimulations) might be a suitable strategy to promote endogenous neurogenesis in AD, and suggest the participation of PLA2 in the neurogenesis promoted by cognitive stimulation.